Social Innovation: Creating New Business Models for Adult and Continuing Higher Education - Sandria S. Stephenson (Adult Education Research Conference, 2010)
Using a qualitative approach to inquiry this paper highlights results of a study, which focuses on (1) the current challenges facing continuing higher education (CHE) divisions; (2) how these divisions engage in social and systematic innovation in an effort to foster social responsibility. It demonstrates a model strategy for mitigating the challenges using Drucker’s (1985) eight sources of systematic innovation. CHE divisions will be better prepared to respond to societies’ needs and pursue their mission and that of their parent institutions.